2022
DOI: 10.1111/dth.15804
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy in patients with psoriasis receiving systemic medications: A nested case‐control study

Abstract: Large-scale, real-world studies on the side effects of systemic therapies (including biologics) in patients with psoriasis are limited. We aimed to calculate the risk of malignancy in patients with psoriasis who were treated with systemic medications.Nested case-control analyses were performed among psoriasis patients without a history of malignancy. We recruited 4188 patients with newly diagnosed psoriasis and successive malignancies, and 8376 matched controls from the National Health Insurance Research Datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In addition, the FDA warns about the increased risk for malignancy, particularly cutaneous and lymphoproliferative neoplasms [42]. The data on this is mixed and may vary based on the indication for which methotrexate is being used-some studies found no increased risk of malignancy among patients receiving methotrexate for psoriasis specifically, while others found increased risk of cutaneous malignancies with methotrexate use across all indications [44][45][46][47][48]. However, for patients on treatment with ICIs, some data suggests that methotrexate may actually increase anti-tumor response; in vitro experiments have demonstrated that methotrexate induces increased maturation of dendritic cells and greater stimulation of T cells [39,49].…”
Section: Methotrexatementioning
confidence: 99%
“…In addition, the FDA warns about the increased risk for malignancy, particularly cutaneous and lymphoproliferative neoplasms [42]. The data on this is mixed and may vary based on the indication for which methotrexate is being used-some studies found no increased risk of malignancy among patients receiving methotrexate for psoriasis specifically, while others found increased risk of cutaneous malignancies with methotrexate use across all indications [44][45][46][47][48]. However, for patients on treatment with ICIs, some data suggests that methotrexate may actually increase anti-tumor response; in vitro experiments have demonstrated that methotrexate induces increased maturation of dendritic cells and greater stimulation of T cells [39,49].…”
Section: Methotrexatementioning
confidence: 99%